An efficient Agrobacterium-mediated transformation of strawberry cv. camarosa by dual plasmid system - Haddadi, Fatemeh; Abdul Aziz, Maheran; Abdullah, Siti Nor Akmar (MDPI, 2015)
An Agrobacterium-mediated transformation method was applied to introduce the luciferase reporter gene under the control of the CaMV35S promoter in the pGreen0049 binary vector into strawberry cv. Camarosa. The in vitro regeneration system of strawberry leaves to be used in the transformation was optimized using different TDZ concentrations in MS medium. TDZ at 16 µM showed the highest percentage (100%) of shoot formation and the highest mean number of shoots (24) produced per explant. Studies on the effects of different antibiotics, namely timentin, cefotaxime, carbenicillin and ampicillin, on shoot regeneration of strawberry leaf explants showed the best shoot regeneration in the presence of 300 mg/L timentin and 150 mg/L cefotaxime. Assessment of the different factors affecting Agrobacterium mediated-transformation of strawberry with the luciferase gene showed the highest efficiency of putative transformant production (86%) in the treatment with no preculture, bacterial OD600 of 0.6 and the addition of 150 mg/L cefotaxime in the pre-selection and selection media. The presence of the luciferase gene in the plant genome was verified by the luciferase reporter gene assay, nested PCR amplification and dot blot of genomic DNA isolated from the young leaves of each putatively transformed plantlet.